2023
DOI: 10.1093/pnasnexus/pgad135
|View full text |Cite
|
Sign up to set email alerts
|

Cis mutagenesis in vivo reveals extensive noncanonical functions of Dscam1 isoforms in neuronal wiring

Abstract: Drosophila Dscam1 encodes tens of thousands of cell recognition molecules via alternative splicing, which are required for neural function. A canonical self-avoidance model seems to provide a central mechanistic basis for Dscam1 functions in neuronal wiring. Here, we reveal extensive noncanonical functions of Dscam1 isoforms in neuronal wiring. We generated a series of allelic cis mutations in Dscam1, encoding a normal number of isoforms, but with an altered isoform composition. Despite normal dendritic self-a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This idea is supported by genetic evidence that altering the variant composition by deleting docking sites in exon 4 or 6 clusters leads to <5% subtle to mild MB defects [ 27 , 36 ]. However, deleting upstream docking sites in the exon 9 cluster causes up to 60% of MB defects [ 28 ]. Diverse neurons exhibit considerable correlation curve differences in individual exon clusters ( Fig 7G–7I ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea is supported by genetic evidence that altering the variant composition by deleting docking sites in exon 4 or 6 clusters leads to <5% subtle to mild MB defects [ 27 , 36 ]. However, deleting upstream docking sites in the exon 9 cluster causes up to 60% of MB defects [ 28 ]. Diverse neurons exhibit considerable correlation curve differences in individual exon clusters ( Fig 7G–7I ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent knockdown of Dscam1 revealed its diverse roles in central neuron arbor differentiation [ 26 ]. Recently, we showed that alterations of Dscam1 exon 9 variants result in obvious mushroom body (MB) axonal defects, partially supporting the specific function of Dscam1 isoforms [ 27 , 28 ]. Genetic analysis of a series of mutant flies with a single exon 6 or 9 variant revealed that 396 and 576 Dscam1 isoforms are insufficient for normal patterning of MB axonal branches [ 22 ].…”
Section: Introductionmentioning
confidence: 99%